Mediação e Ensino da Arte: Um Exercício de Partilha do Sensível (Palíndromo, 2013)
The present work aims at reflecting on the aesthetic education taking into consideration formal teaching as well as environments out of formal school and presupposing that although artistic production aims at meeting its creator needs, it has also to be shared with other people. Thus, the art educator role is to mediate the sharing of sensibility considering not only the production process but also the student as a part of the process that completes and/or changes the work meaning. Therein, the mediation exercise – work, author, readers - may greatly contribute to increase the visibility of the human meaning contained in the art work. A great part of the present study is dedicated to examine mediation as an instrument of artistic-visual production analysis, production of new meanings and distribution of cultural goods. Finally, mediation also builds the student autonomy for reading imagesthus providing a permanent process of finding meanings as well as appropriating and sharing art, what is one of its main contributions to aesthetic education.
Keywords: Aesthetic education; Human sensibility building; Image reading; Mediation; Art Production and Consumption